Directing some biomechanical indicators to improving heading ball from flying position of soccer players - Abd El-Hamid Hassan Ali, M.; Ibrahim Ali Hassan, H. (World Journal of Sport Sciences, 2010)
Defining the effect of using some specific exercises on some biomechanical indicators on the accuracy of soccer players in heading the ball from flying and reaching forecasting mathematical equations that represent a guiding scientific basis to improving the particulars of ball heading from flying performance for the search sample. The researchers used the Experimental on the fast video analysis 125 Hz, The search sample included 4 players from Zagazig University team, each player had performed 4 trials to heading the ball from flying, the researchers determined the place where the player would perform the skill of hitting the ball by head from flying. This point was determined as 3-yard distance from the mark of the penalty kick inside the field and towards the goal, the researchers placed 2 cameras by a wire that is equipped with a control device. The best vertical distance for the researchers recommend the training of the players to choose the right timing when performing the skill of heading the ball from flying, the soccer player needs to decrease the velocity of the shoulder during flying before the moment of heading the ball from flying, which results in a bigger chance to hit the ball with greater accuracy in the direction of the divided goal, the angel of the neck and right foot ankle has a main and effective role in directing the ball towards the target, as the value of this angel of 108.741° &149.285° degrees.